The processing of temporal fine-structure information in the human auditory system - Magezi, David Amooti. (2010)
The auditory nerve conveys fine-grained temporal information that reflects individual cycles of the basilar membrane vibration. The current project is concerned with how this temporal fine-structure information is processed in the human auditory system. Integration of fine-structure temporal information across the ears (binaural processing) plays a crucial role in sound localisation and signal detection in noise. However, in monaural processing, the role of temporal fine-structure information remains uncertain, because spectral information is usually also available. The first study in this project used behavioural methods, along with model simulations, to show that the binaural system exploits phase differences between disparate frequency channels for processing fine-structure interaural temporal differences (ITDs). The second study explored the neural representation of ITDs by using electroencephalography (EEG) to measure the transient brain response to a change in ITD in an otherwise continuous sound. The results suggest that fine-structure ITDs are coded by a non-topographic opponent-channel mechanism, based on the overall activity levels in two broadly tuned hemispheric channels. The third study used rapid event-related functional magnetic resonance imaging (fMRI) to investigate the topography of the transient ITD change response measured in the second study. The ITD change response was compared with the transient response to the onset of pitch in an otherwise continuous sound. It was found that the topographies of the transient ITD and pitch responses were very similar to the topographies of the corresponding sustained responses measured in previous epoch-related fMRI studies. The last two studies examined whether temporal fine-structure information is used for frequency coding in monaural processing. The fourth study aimed to eliminate temporal fine-structure cues from the neural representation of low-frequency pure tones by presenting the tones in conditions of binaural unmasking, because a previous study had shown that temporal envelope cues to pitch are inaccessible in such masking conditions. However, frequency discrimination performance for pure tones was found to be similar in monaural and binaural masking conditions. The fifth study suggests that this was because frequency discrimination of low-frequency pure tones relies on spectral rather than temporal cues. In this study, frequency discrimination performance was measured for partially masked pure tones and was found to reflect the level-dependent changes in the shape of the pure-tone excitation pattern.